Security in e-learning - Weippl, Edgar R. (Springer, 2005)
As e-learning increases in popularity and reach, more people are taking online courses and thus need to understand security issues relevant to this topic. Security in E-Learning discusses typical threats to e-learning projects and introduces how these issues have been and should be addressed. This knowledge is essential to conduct a security risk analysis effectively, because participants need to be aware of common threats, protection mechanisms and effort/cost issues. Based on the security risk analysis, appropriate preventive measures are thoroughly discussed in this book. Security in E-Learning is designed for a professional audience composed of researchers and practitioners in industry and IT professionals. This volume is also suitable for upper undergraduate-level and graduate-level students in computer science.